2021
DOI: 10.1101/2021.08.31.458247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subtle immunological differences in mRNA-1273 and BNT162b2 COVID-19 vaccine induced Fc-functional profiles

Abstract: The successful development of several COVID-19 vaccines has substantially reduced morbidity and mortality in regions of the world where the vaccines have been deployed. However, in the wake of the emergence of viral variants, able to evade vaccine induced neutralizing antibodies, real world vaccine efficacy has begun to show differences across the mRNA platforms, suggesting that subtle variation in immune responses induced by the BNT162b2 and mRNA1273 vaccines may provide differential protection. Given our eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…56 Moreover, the BNT162b2 and mRNA1273 mRNA vaccines appear to induce different functional profiles in humans with higher RBD-and NTD-specific IgA as well as functional antibodies (ADNP and antibody-dependent natural killer cell activity [ADNK]) seen in mRNA-1273 vaccine recipients. 57 Thus, and independent of the lower neutralizing antibody levels observed in the sera of individuals with CID treated with TNFi, diminished Fc effector function profiles could also contribute to a higher frequency of breakthrough infections in this and other immunosuppressed vaccinated populations. [58][59][60] The lower serological responses to the BNT162b2 vaccine seen in many of the individuals with CID in our cohort appears the be worse against the two viruses with spike genes of B.1.351 and B.1.617.2.…”
Section: Discussionmentioning
confidence: 99%
“…56 Moreover, the BNT162b2 and mRNA1273 mRNA vaccines appear to induce different functional profiles in humans with higher RBD-and NTD-specific IgA as well as functional antibodies (ADNP and antibody-dependent natural killer cell activity [ADNK]) seen in mRNA-1273 vaccine recipients. 57 Thus, and independent of the lower neutralizing antibody levels observed in the sera of individuals with CID treated with TNFi, diminished Fc effector function profiles could also contribute to a higher frequency of breakthrough infections in this and other immunosuppressed vaccinated populations. [58][59][60] The lower serological responses to the BNT162b2 vaccine seen in many of the individuals with CID in our cohort appears the be worse against the two viruses with spike genes of B.1.351 and B.1.617.2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study still in pre-print format showed higher epitope spreading, IgA immunity and specific Ab function (i.e. enhanced Ab-dependent neutrophil phagocytosis and Ab-dependent NK cell degranulation) in patients vaccinated with the mRNA-1273 in comparison to the BNT162b vaccine (55). In concordance with the higher immunogenicity of mRNA-1273 vaccine, a recent study observed lower 24-week COVID-19 outcomes (defined as documented SARS-CoV-2 infection, symptomatic COVID-19, hospitalization and/or admission for ICU for COVID-19, or death from COVID-19) in persons vaccinated with the mRNA-1273 vaccine than in those given the BNT162b2 vaccine (56).…”
Section: Immune Response To Sars-cov-2 Mrna Vaccination In Healthy Ad...mentioning
confidence: 97%
“…Durable antibody responses are mediated through memory B cells and long-lived plasmablasts. These subsets continuously produce neutralizing antibodies and non-neutralizing antibodies that will mobilize effector functions of innate immune cells such as antibody-dependent cellular cytotoxicity and antibody-dependent neutrophil phagocytosis 12,13 . This contributes to protection during acute infection and perhaps reduce the risk of reinfection.…”
Section: Sars-cov-2 Vaccines: What Do We Know About Efficacy?mentioning
confidence: 99%